Local and Global Interactions in an Evolutionary Resource Game - Joëlle Noailly; Jeroen C.J.M. van den Bergh; Cees A. Withagen (Fondazione Eni Enrico Mattei (FEEM), 2005)
Conditions for the emergence of cooperation in a spatial common-pool resource game are studied. This combines in a unique way local and global interactions. A fixed number of harvesters are located on a spatial grid. Harvesters choose among three strategies: defection, cooperation, and enforcement. Individual payoffs are affected by both global factors, namely, aggregate harvest and resource stock level, and local factors, such as the imposition of sanctions on neighbors by enforcers. The evolution of strategies in the population is driven by social learning through imitation. Numerous types of equilibria exist in these settings. An important new finding is that clusters of cooperators and enforcers can survive among large groups of defectors. We discuss how the results contrast with the non-spatial, but otherwise similar, game of Sethi and Somanathan (1996).
Keywords: C72; Q2; 330; Common property; Cooperation; Evolutionary game theory; Global interactions; Local interactions; Social norms; Gemeingüter; Kooperation; Evolutionäre Spieltheorie; Soziale Norm; Theorie